Enron and World Finance A Case Study in Ethics - Dembinski, P.; Lager, C.; Cornford, A.; Bonvin, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
Four years after the debacle, the term 'Enron' has earned its place in the everyday vocabulary of business ethics. Hardly anyone understands the business intricacies of what really happened with the sophisticated energy conglomerate. Even fewer are those able to envision, beyond the business case, the ethical questions and dilemmas facing actors at any one stage of the drama. Using the collapse of Enron as a case study, this book not only shows how and where ethics came into play, but also draws lessons and discusses possible remedies that may prevent the whole financial system from falling apart as a result of either excessive greed or over-regulation.
Keywords: Accounting; Bookkeeping .; Leadership; Business ethics; Finance; Accounting/Auditing.; Business Strategy/Leadership.; Business Ethics; Finance, general